Teachers’ perceptions of school assessment climate and realities of assessment practices in two educational contexts - Asamoah, Daniel; Shahrill, Masitah; Abdul Latif, Siti Norhedayah (Frontiers in Education, 2024)
School and national assessment climates are critical contextual factors that shape teachers' assessment preferences. In this study, 431 secondary school teachers from Ghana (n = 308) and Brunei (n = 123) were surveyed to examine how their perceptions of school assessment climates influenced their assessment practices. Semi-structured interviews were also conducted with six Bruneian and eight Ghanaian teachers to understand how they practiced assessment amid their school assessment climates. Teachers were found to practice assessment and perceive their school assessment climates differently. They were either identified as moderately fair but less precise, standard-focused and more precise, formative-oriented but moderately precise assessors, or preferred contextual and need-based assessment. Teachers reported positive perceptions of the nature of school assessment climates that existed in their schools. However, the examination-oriented climates that prioritised summative assessment compelled teachers to practice assessment against their beliefs. This resulted in academic dishonesty, excessive pressure, and mental health problems among teachers and students. The findings provide implications for assessment policy and practice in terms of how result-driven educational climates compel school leaders, teachers, and students to be gatekeepers and implementers of highly marketised and politicised education and assessment systems, which hinder lifelong learning and teacher-preferred assessment practices.